The knife - Stine, R. L. (Pocket Books New York, 1992)
In The Knife, Laurie Masters, a high school student with dreams of becoming a doctor, volunteers at Shadyside Hospital. However, when she starts noticing strange occurrences and becomes suspicious of a mysterious surgeon, her life takes a terrifying turn. Laurie is caught between her aspirations and the dark secrets lurking within the hospital, where her curiosity could cost her more than just her future.